Simultaneous Saccharification and Fermentation of Sugarcane Bagasse by Saccharomyces Cerevisiae and Zymomonas Mobilis - Elfrida Ginting; Ecclesia Siregar; Ratna Sari Dewi; Lisnawaty Simatupang; Marnida Yusfiani; Jhony Hartanta Sembiring (Indonesian Journal of Chemical Research, 2026)
Sugarcane bagasse represents a promising lignocellulosic feedstock for second-generation bioethanol production. This study evaluated the performance of immobilized Simultaneous Saccharification and Fermentation (SSF) systems using Saccharomyces cerevisiae and Zymomonas mobilis for ethanol production from alkali-pretreated sugarcane bagasse. Delignification using 10% NaOH enhanced cellulose accessibility for enzymatic hydrolysis by immobilized Aspergillus niger. SSF was conducted under anaerobic conditions at 30°C for 80 h. Reducing sugar dynamics, physicochemical properties, FTIR spectra, and GC analysis were used to evaluate ethanol formation and quality. The SSF system employing S. cerevisiae produced a higher ethanol concentration (2.83% v/v) and purity (99.77%) compared to Z. mobilis (2.20% v/v; 89.92%). Although higher residual reducing sugars were observed in the Z. mobilis system, ethanol conversion efficiency remained lower, indicating metabolic limitations under SSF conditions. FTIR and GC analyses confirmed ethanol formation with high water content in both distillates. These results demonstrate that microbial robustness plays a critical role in immobilized SSF performance, with S. cerevisiae exhibiting superior fermentative stability and ethanol yield compared to Z. mobilis.